Digital systems design using VHDL - Roth, Charles H. (Thomson Learning, 2008)
This texbook is intened for a senior-level course in digital systems design. The book covers both basic principles of digital system design and the use of a hardware description language, VJDL in the design process. After basic principles have been covered, design is best taught by using examples.